A aplicabilidade de verificadores na avaliação da qualidade do manejo florestal comunitário na Floresta Nacional do Tapajós - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
In order to promote the use of good sustainable forest management practices, verify the quality of the enterprise's forestry operations and the standards required by law, in 2006 EMBRAPA created the Field Inspection Manual for Timber Forest Management Plans in Amazon, focused almost exclusively on business management, not taking into account specific aspects of community forest management (CFM). In this way, the objective of the present work was to propose a methodology to evaluate community forest management plans in federal conservation units, having as a reference point the Field Inspection Manual for Forest Management Plans and the guidelines inaugurated with the advent of Normative Instruction ICMBio 16/2011. This study was carried out in the Tapajós National Forest – Belterra, Pará. Those responsible for forest enterprises, professors, researchers and environmental analysts from bodies such as UFOPA, ICMBio and COOMFLONA were invited to analyze the verifiers in the manual, selecting which ones were suitable for the MFC in conservation units, which could be used in full, excluded or adapted accordingly. with the guidelines of Normative Instruction ICMBio 16/2011. It was observed that the evaluation units that most needed adaptations were: site in clearing operations, camping, infrastructure and site in skidding operations. The only unit that did not have applicable verifiers was the office unit. It is concluded, therefore, that 69% of the verifiers suffered some suggestion of adaptation, even if small in some cases, but all of them extremely relevant to help in the greater efficiency and quality of the forest management carried out in the Conservation Units.
Keywords: Floresta Nacional do Tapajós; Manual de vistoria; Amazônia; CNPQ:: ENGENHARIAS